NELF knockout is associated with impaired pubertal development and subfertility. (15th May 2015) - Quaynor, Samuel D.; Ko, Eun Kyung; Chorich, Lynn P.; Sullivan, Megan E.; Demir, Durkadin; Waller, Jennifer L.; Kim, Hyung-Goo; Cameron, Richard S.; Layman, Lawrence C.
Highlights: NELF is an important regulator of puberty and fertility. Male Nelf knockout (KO) mice have normal puberty, but manifest subfertility. Female Nelf KO mice have delayed puberty, small uteri, and lower GnRH neuron number. Female heterozygous KO mice also have delayed puberty and manifest subfertility. NELF disruption more severely affects females, but both sexes manifest subfertility. Abstract: Puberty and reproduction require proper signaling of the hypothalamic–pituitary–gonadal axis controlled by gonadotropin-releasing hormone (GnRH) neurons, which arise in the olfactory placode region and migrate along olfactory axons to the hypothalamus. Factors adversely affecting GnRH neuron specification, migration, and function lead to delayed puberty and infertility. Nasal embryonic luteinizing hormone-releasing factor (NELF) is a predominantly nuclear protein. NELF mutations have been demonstrated in patients with hypogonadotropic hypogonadism, but biallelic mutations are rare and heterozygous NELF mutations typically co-exist with mutations in another gene. Our previous studies in immortalized GnRH neurons supported a role for NELF in GnRH neuron migration. To better understand the physiology of NELF, a homozygous Nelf knockout (KO) mouse model was generated. Our findings indicate that female Nelf KO mice have delayed vaginal opening but no delay in time to first estrus, decreased uterine weight, and reduced GnRH neuron number. In contrast, male mice were normal at puberty. Both sexes of mice had impaired fertility manifested as reduced mean litter size. These data support that NELF has important reproductive functions. The milder than expected phenotype of KO mice also recapitulates the human phenotype since heterozygous NELF mutations usually require an additional mutation in a second gene to result in hypogonadotropic hypogonadism.